VIDEO ANIMATION AS TEACHING MEDIA IN ELT - titis sulistyowati; Testiana Deni Wijayatiningsih (Prominent, 2019)
The issue of TPACK (Technology Pedagogical Content Knowledge) offers a problem solution for teachers who are interested in implementing blended learning. Education and Technology have become an important aspect in every student's daily life beyond the school and within the classroom. Experts now create software that facilitates teachers in creating animated videos which contain pedagogical knowledge. One of them is Videoscribe which can be used to present learning content by combining interesting images, sounds, and graphs to attract students to enjoy the learning process. The features provided by this software are varied, they enable teachers to design learning media that can be adjusted to meet the goal of the lesson. This paper will elaborate on how teachers can design an interesting and engaging learning media to meet the students’ needs and to achieve learning objectives by using the software.